TELAAH KONSEPSI NEGARA HUKUM DAN DEMOKRASI DALAM PEMBENTUKAN BLUE CONSTITUTION DI INDONESIA - Fathan Ali Mubiina (SASI, 2020)
The supporting idea of this topics relates to the term of exclusive economic zone which is defined as a territorial sea outside, coastal states that have sovereignty over all natural resources in them and have the right to the application of Coastal state jurisdiction. This zone is located at 200 miles from the base of the territorial sea. Indonesia requires the Blue Constitution or maritime constitution as a constitutional basis for the use of maritime territory in Indonesia. This is what is said to be horizontally integrated territory. There is also the condition of a country's territorial territory separated from other countries' territorial territories. The essence of the state is to control a territory and be recognized internationally. There is existing country if it occupies an area which is its right to the interests of social and geographical unity. The sea area of a country such as Indonesia contained in the provisions of the 1945 Constitution is referred as the blue constitution inside.